Latitudinal variability in the seroprevalence of antibodies against Toxoplasma gondii in non-migrant and Arctic migratory geese - C Sandstrom; A Buma; Bethany Hoye; J Prop; H van der Jeugd; B Voslamber; J Madsen; M Loonen (2013)
Latitudinal variability in the seroprevalence of antibodies against Toxoplasma gondii in non-migrant and Arctic migratory geese